Children of Buddha, or Caretakers of Women?: Self-Understandings of Ordained Buddhist Women in Contemporary Japan - Schrimpf, Monika (Journal of Religion in Japan, 2015)
This paper deals with the self-understandings of ordained Buddhist women (nisō 尼僧, ama 尼) in contemporary Japan. Their situation is characterized by discrimination and limited access to clerical positions on the one hand and, with the exception of monastic nuns, by their lack of a clearly defined role on the other. Although the training required to attain the status of a fully ordained cleric is firmly regulated by each Buddhist school, ordained women’s subsequent way of life is not. They may be married and have their own families. They may be the head priestess of a temple, the wife of a temple priest, or work in a temple. They may live according to Buddhist precepts in private, or have secular jobs. Under these conditions, ordained women have found ways of empowering themselves by interpreting their role in accordance with their social contexts and by re-evaluating conservative conceptions of gender.